Effect of Global Postural Reeducation on cardiovascular system of healthy subjects - Elizângela Márcia de Carvalho Abreu; Tatiana Sousa Cunha; Alderico Rodrigues de Paula Júnior; Marco Antonio de Oliveira
Objective To evaluate the effect of Global Postural Reeducation (GPR) on cardiovascular system by heart rate variability (HRV), blood pressure (BP) and heart rate (HR). Materials and methods Seventeen healthy men (22.47 ± 3.02 years) were submitted to the postures frog on the floor, frog on the air, sitting, standing against the wall and inclined standing, two postures per session. The systolic and diastolic blood pressure (SBP and DBP) and HR were recorded. The intervals between heartbeats were collected during the whole session (Polar S810i). The frequency domain was analyzed (Wavelet Transform), the low frequency (LF) and high frequency (HF) were obtained. The data were analyzed by ANOVA and Tukey (p < 0.05). Results Increased LF/HF ratio was observed in the frog on the floor (1 ± 0.1 vs. 2 ± 0.3 p < 0.05) and on the air postures (1 ± 0.1 vs. 2 ± 0.2 p < 0.01). There was an increase in SBP in the postures frog on the floor (123 ± 2 vs. 136 ± 4 p < 0.05), frog on the air (122 ± 2 vs. 133 ± 3 p < 0.05), standing against the wall (123 ± 2 vs. 136 ± 4 p < 0.05), inclined standing (124 ± 3 vs. 146 ± 5 p < 0.05). There was increase of DBP in the postures frog on the floor (69 ± 2 vs. 81 ± 2 p < 0.01), frog on the air (72 ± 2 vs. 83 ± 3 p < 0.05), sitting (85 ± 2 vs. 102 ± 3 p < 0.01). There was increase in HR in the postures frog on the air (67 ± 2 vs. 77 ± 3 p < 0.05) and inclined standing (88 ± 3.5 vs. 101 ± 3 p < 0.05). Conclusion The increase in LF/HF ratio and also the BP and HR indicates high sympathetic activity, possibly related to the work isometric developed during GPR method. [P]